Calling Baumol: What Telephones Can Tell Us about the Allocation of Entrepreneurial Talent in the Face of Radical Institutional Changes - Alina Sorgner; Michael Wyrwich (Institute of Labor Economics (IZA), 2021)
The aim of this paper is to test a key aspect of Baumol's theory that the allocation of entrepreneurial efforts toward its productive (e.g., start-up activity) or unproductive (e.g., rent-seeking) use depends on institutional conditions. In contrast to previous research, we study a context where a radical and exogenous institutional change took place that dramatically changed the rewards and opportunities of running a firm. We analyze at the individual level who decides to start a venture in East Germany after the fall of the Berlin Wall. We find that a significant number of people that demonstrated a strong commitment to the anti-entrepreneurial socialist regime were active in launching new ventures soon after the fall of the Berlin Wall. This pattern cannot be explained by having elite status during the socialist regime. We argue that this commitment to socialism reflects rent-seeking, a type of unproductive entrepreneurship. Once institutions change radically, their entrepreneurial efforts are redirected towards productive entrepreneurship (start-up activity). Regime commitment is captured by information from the 1990 wave of the German Socioeconomic Panel (GSOEP) that includes information on whether East German respondents had a telephone during the socialist era, a typical reward for pronounced efforts for the socialist regime. We find that this group of people were more likely to have an entrepreneurship- prone personality profile, had a higher propensity of becoming selfemployed, and were more successful entrepreneurs. Our results confirm Baumol's theory in a setting that resembles the historical examples Baumol used to make his general argument.
Keywords: L26; P20; P31; 330; entrepreneurship; transition; institutional conditions